Gold as an investment instrument in times of financial instability - Zolotova, E. A.; Samchenko, L. A.; Pasko, E. A.; Zolotova, A. G. (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. The gold market is one of the oldest and most stable markets in the world, which attracts the attention of investors, traders and central banks from all over the world. Gold has been serving for many years as a stable asset and a means of preserving capital in the face of global economic crises and fluctuations in financial markets. This article examines the key factors influencing the dynamics of the gold market, its features and development prospects. Goal. Consider gold as a savings and investment asset, analyze the problems and prospects of its development. Materials and methods. The analysis of the sources of Russian literature is carried out. In the process of writing the paper, such research methods as statistical analysis, correlation and regression analyses were used. Results and discussion. In the course of the study, it was established that gold has historically consolidated its position, since it was used as a monetary equivalent in ancient times. Advantages and disadvantages of various investment assets related to gold. The results of the factor analysis of the gold sale price. Conclusion. Gold has great prospects for development as an investment and savings asset due to its high liquidity, investor confidence and other factors that have developed historically